The Role of Non-Text Picture Story Books in Enhancing Narrative Structuring Skills of Elementary School Students - Sukniasih Sukniasih; Sri Wardani; Bambang Subali (Journal of General Education and Humanities, 2026)
Many elementary students are able to decode written text fluently but struggle to construct coherent narratives with clear sequencing and causal relationships. This study aimed to develop and evaluate a culturally grounded non-text picture storybook to enhance narrative structuring skills among elementary school students. The research employed a Research and Development (R&D) design using the Plomp model, consisting of preliminary investigation, design, realization, testing, and implementation phases. The product was developed based on Cirebon’s coastal ethnoscience and tested through a limited trial involving 30 second-grade students, followed by broader implementation with 200 students from ten public elementary schools in Cirebon City, Indonesia. Data were collected through expert validation, practicality questionnaires, pre-test and post-test assessments, and classroom observations. The results indicated that the storybook met high validity standards in terms of content (4.2), media design (4.0), and language (4.0). Practicality ratings from teachers (4.7) and students (4.1) showed positive user responses. Quantitative findings revealed a significant improvement in students’ narrative structuring skills, with a large effect size. The study concludes that integrating visual scaffolding with culturally relevant content effectively strengthens students’ ability to organize and express narratives. This research contributes to visual literacy development and culturally responsive pedagogy in elementary education.